Development of a fibroblast activation protein-targeted PET/NIR dual-modality probe and its application in head and neck cancer - Li, Danni; Li, Xuran; Li, Jiaojiao; Wang, Yanhong; Tan, Fei; Li, Xiao (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: The combination of near-infrared (NIR) and positron emission tomography (PET) imaging presents an opportunity to utilize the benefits of dual-modality imaging for tumor visualization. Based on the observation that fibroblast activation protein (FAP) is upregulated in cancer-associated fibroblasts (CAFs) infiltrating all solid tumors, including head and neck squamous cell carcinoma (HNSCC), we developed the novel PET/NIR probe [68Ga]Ga-FAP-2286-ICG. Preclinically, the specificity, biodistribution and diagnostic properties were evaluated. Methods: Cell uptake assays were completed with the U87MG cell to evaluate the specificity of the [68Ga]Ga-FAP-2286-ICG. The tumor-targeting efficiency, biodistribution and optimal imaging time window of the [68Ga]Ga-FAP-2286-ICG were studied in mice bearing U87MG xenografts. HNSCC tumor-bearing mice were used to evaluate the feasibility of [68Ga]Ga-FAP-2286-ICG for tumor localization and guided surgical resection of HNSCC tumors. Results: The in vitro experiments confirmed that [68Ga]Ga-FAP-2286-ICG showed good stability, specific targeting of the probe to FAP, and the durable retention effect in high-expressing FAP tumors U87MG cell. Good imaging properties such as good tumor uptake, high tumor-to-background ratios (5.44 ± 0.74) and specificity, and tumor contouring were confirmed in studies with mice bearing the U87MG xenograft. PET/CT imaging of the probe in head and neck cancer-bearing mice demonstrated specific uptake of the probe in the tumor with a clear background. Fluorescence imaging further validated the value of the probe in guiding surgical resection and achieving precise removal of the tumor and residual lesions. Conclusion: In a preclinical model, these attractive [68Ga]Ga-FAP-2286-ICG PET/NIR imaging acquired in head and neck cancer make it a promising FAP-targeted multimodal probe for clinical translation.